FORMULATION DEVELOPMENT AND EVALUATION OF FAST DISINTEGRATING TABLETS OF CINITAPRIDE HYDROGEN TARTARATE BY USING DIRECT COMPRESSION TECHNIQUE - Chinnala, Krishna Mohan; Vodithala, Sirish (International Journal of Current Pharmaceutical Research, 2017)
Objective: In the present study, efforts were taken to develop fast disintegrating tablets of Cinitapride hydrogen tartrate, is a gastro-prokinetic agent and antiulcer agent with an objective to achieve rapid disintegration, and further improving the bioavailability of the drug. Also, to resolve the swallowing problems (Dysphasia) in pediatric, geriatric patients by rapid disintegration in saliva and improve the patient compliance. Methods: Fast disintegrating tablets were prepared by direct compression method using superdisintegrants like crospovidone (CP), croscarmellose sodium (CCS), sodium starch glycolate (SSG) and combination of super-disintegrants in different concentrations. The prepared formulations were evaluated for the pre-compression parameters like bulk density, tapped density, Carr's compressibility, Hausner's ratio and angle of repose. The prepared batches of fast disintegrating tablets of Cinitapride hydrogen tartarate were evaluated for hardness, weight variation, thickness, friability, drug content, disintegration time, wetting time, water absorption ratio, and in vitro dissolution profile. Results: Bulk density and tapped density were found in the range of 0.412–0.432 g/cc and 0.507–0.528 g/cc respectively. In all formulations, tablet weight and thickness were within mean±9.5% and mean±5% respectively. Wetting time values lie between 19.76 to 39.53 sec. Water absorption ratio ranged from 57.30 to 78.82 %. The in vitro disintegration time for all the 12 formulations varied from 17.43 to 38.61 seconds. Formulation F8 which contained crosspovidone have recorded drug release 96.94±0.47% at the end of 30 min. Conclusion: The formulation containing crospovidone (F8) showed better performance in terms of disintegration time and drug release when compared to other formulations.